2013
DOI: 10.1002/chem.201302207
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Excitation‐Independent Photoluminescent Graphene Quantum Dots with Visible‐Light Excitation/Emission for Cell Imaging

Abstract: We report the first pyrrole-ring surface-functionalized graphene quantum dots (p-GQDs) prepared by a two-step hydrothermal approach under microwave irradiation in an ammonia medium. The most distinct feature of the functionalized GQDs is that both the excitation and emission wavelengths fall into the visible-light region. The p-GQDs are excited by visible light at λ(ex) 490 nm (2.53 eV) to emit excitation-independent photoluminescence at a maximum wavelength of λ(em) 550 nm. This is thus far the longest emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 24 publications
1
40
0
Order By: Relevance
“…Our previous investigation showed the pyrrolic ring formed via dehydrolysis between neighbor carboxyl and amide groups 18 . The solid 13 C nuclear magnetic resonance spectrum demonstrated that the pyrrolic ring belongs to pyrrolidone 32,33 . With the pyrrolidone formation, the relative amount of carbonyl (C5O) increases, which is consistent with the results of O 1s high-resolution XPS spectra.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous investigation showed the pyrrolic ring formed via dehydrolysis between neighbor carboxyl and amide groups 18 . The solid 13 C nuclear magnetic resonance spectrum demonstrated that the pyrrolic ring belongs to pyrrolidone 32,33 . With the pyrrolidone formation, the relative amount of carbonyl (C5O) increases, which is consistent with the results of O 1s high-resolution XPS spectra.…”
Section: Resultsmentioning
confidence: 99%
“…S3). That means this band is not only related to the n R p* transition of C5O but also the transition of orbitals (HOMO) to the lowest unoccupied molecular orbitals (LUMO) of these groups 14,33 . Comparing the UV-Vis spectra of three kinds of N-GQDs, the adsorption band at 350 nm has a slight red-shift to 360 nm (Figure 3d), indicating that this band affects by the chemical composition of N-GQDs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By functionalizing GQDs, their emission wavelength can be further tuned. Chen et al prepared GQDs of 2 to 6 nm in size, which, subsequent to the exfoliation process, were treated with a surface functionalization step in ammonia solution. This microwave‐assisted treatment resulted in a redshift of the emission maximum to 550 nm.…”
Section: Preparation Of Materialsmentioning
confidence: 99%
“…For instance, Jiang et al [130] synthesized single-or double-layered size-controllable amine-functionalized GQDs by an eco-friendly method with graphene oxide sheets, ammonia and hydrogen peroxide as starting materials, and found a negligible toxicity to HeLa cells for amine-functionalized GQDs. In addition, Chen et al [151] prepared the pyrrole-ring surface-functionalized graphene quantum dots (p-GQDs) by a twostep hydrothermal approach under microwave irradiation of graphene oxide in an ammonia medium. The obtained p-GQDs emittance featured excitation-independent photoluminescence at a maximum wavelength of 550 nm when excited by visible light (490 nm), and stable photoluminescence between pH 4-10 with an ionic strength of 1.2 mol/L KCl was observed.…”
mentioning
confidence: 99%